An efficient oppositional crow search optimisation-based deep neural network classifier for chronic kidney disease identification. (10th June 2021) - Arulanthu, Pramila; Perumal, Eswaran
Internet of things (IoT) enables gathering the patient data that can incite logically exact and tiny prosperity events. Distributed computing along with the IoT is another example of gainful regulating and treatment of sensor data. This paper presents IoT and cloud-based capable choice emotionally supportive network for identification of chronic kidney disease (CKD). Additionally, deep neural network (DNN) classifier is utilised for the assurance of CKD. Oppositional crow search (OCS) optimisation approach selects the necessary features and takes out the undesirable features and also it enhances the process of DNN. This model gathers the patient information by utilising the IoT gadgets with cloud and related therapeutic records from the UCI vault. The proposed OCS-DNN measured by the accuracy, specificity, execution time and sensitivity which produces 97.71% accuracy, 98.88% sensitivity and 93.44% of specificity when contrasted with other classifiers and results exhibit that the proposed OCS-DNN is much better.